A Discussion of Bisexual Populations With Wolbachia Infection as an Evolution Algebra - ESİN, SONGÜL; Kanuni M.; Özdinç B. (Taylor and Francis Ltd., 2024)
In this paper, Wolbachia infection in a bisexual and diploid population with a fixed cytoplasmic incompatibility rate w and maternal transmission rate d is studied as an evolution algebra. As the cytoplasmic incompatibility (CI) of the population causes deaths in the offspring, the evolution algebra of this model is not baric, and is a dibaric algebra if and only if the cytoplasmic incompatibility rate w is 1 and (Formula presented.). The idempotent elements are given in terms of d and w. Moreover, this algebra has no absolute nilpotent elements when CI expression (Formula presented.). © 2024 Taylor & Francis Group, LLC.
Keywords: Absolute Nilpotent Element; Bisexual Population; Evolution Algebra; Idempotent Element; Wolbachia Infection